Morphology of the articular cartilage of the knee joint in rats with extraarticular femoral bone deformity - Romanenko, Konstantin; Ashukina, Nataliya; Batura, Inna; Prozorovsky, Dmytro (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Objective: to assess the structural and functional state of the rat knee after modeling posttraumatic extraarticular deformation of the femur. Methods: experiment was performed in 39 white mature (6 months old) male rats. To model the deformation of varus (test group, 15 rats) after transverse osteotomy of the femur, a bent angled rod was introduced into the medullary canal, the control animal (15) was straight. The comparison group was intact rats (9) of the corresponding age and sex. After 1, 3 and 6 months. After the operation, histological examination was performed. Results: In 1 month after modeling the deformation in the articular cartilage of the knee joint, destructive changes of 1–2 degree according to OARSI were noted. In contralateral extremity, AC had a structure characteristic of the age norm. After 3 months a decrease in the width of articular cartilage (in comparison with intact group by 1.21 times, p < 0.01), loss of glycosaminoglycans, a violation of the structure and ordering of collagen fibers, accumulation of type I collagen was established. After 6 months the most pronounced disorders were found in the cerebral cortex on the medial condyle of the deformed femur — a 1.63 fold decrease in its width compared with the intact group (p < 0.001), in places the replacement with fibrous cartilage. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> in animals with simulated extraarticular deformation of the femur in the knee joint of the injured limb after 1 month revealed destructive changes that progressed with time. After 1 month the maximum manifestation of disorders was noted in the area of the femur surface under the patella, and after 3 and 6 months he medial condyle. In the articular cartilage of the knee joint of the contralateral limb, destructive changes were recorded 3 months after the reproduction of the deformation, but the severity of the manifestations was less.